(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Brassicas form the most important group of vegetable crops in Montenegro. The cabbage (Brassica oleracea var. capitata) is most commonly grown, although other brassicas, particularly kale, Brussels sprout, cauliflower and broccoli, have been increasingly produced since recently. One of the specialties of vegetable production in Montenegro is growing of collard (Brassica oleracea var. acephala), which is the simplest variety of the Brassica oleracea species and in the nearest relation with their wild ancestor – the sylvestris variety. Diseases are the main restrictive factors for successful production of these vegetables. Susceptibility of the cultivars and inadequate control often result in more or less damaged crops in some plots. Causal agents of brassica diseases, especially bacterial, have not been investigated in Montenegro until 2009. Since the symptoms observed in 2009 were „V” shaped leaf edge necrosis and black rot of vascular tissue, it was assumed that they were caused by plant pathogenic bacterium Xanthomonas campestris pv. campestris. Samples of the infected plants were collected from different localities in Montenegro. Isolation and identification of the bacterium were performed using laboratory methods according to Schaad (1980), Lelliott and Stead (1987) and Arsenijević (1997). Examination of chosen bacterial isolates was conducted using both, classical bacteriological methods (examination of their pathogenic, morphological, cultivation and biochemical and physiological characteristics), and ELISA test. The obtained results confirmed the presence of X.campestris pv. campestris (Pammel, 1895) Dowson 1939, on cabbage, kale, broccoli and collard in Montenegro. This is the first experimental evidence that collard is the host of X. campestris pv. campestris in Montenegro.